2014
DOI: 10.1590/s0103-05822014000100010
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and insulin resistance in obese adolescents

Abstract: Objective: To verify the prevalence of metabolic syndrome and insulin resistance in obese adolescents and its relationship with different body composition indicators. Methods: A cross-sectional study comprising 79 adolescents aged ten to 18 years old. The assessed body composition indicators were: body mass index (BMI), body fat percentage, abdominal circumference, and subcutaneous fat. The metabolic syndrome was diagnosed according to the criteria proposed by Cook et al. The insulin resistance was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 22 publications
3
72
0
12
Order By: Relevance
“…In our study, the prevalence of metabolic syndrome (46.9%) in populations with obesity was higher than that in a previous report by Chung et al [23], and lower than that previously reported by Hsiao et al [24], but it was similar to that in a previous report by Gobato et al [25]. Currently, research on the association between beta cell function and the increase of metabolic syndrome components is lacking.…”
Section: General Characteristics Of Research Subjectssupporting
confidence: 75%
“…In our study, the prevalence of metabolic syndrome (46.9%) in populations with obesity was higher than that in a previous report by Chung et al [23], and lower than that previously reported by Hsiao et al [24], but it was similar to that in a previous report by Gobato et al [25]. Currently, research on the association between beta cell function and the increase of metabolic syndrome components is lacking.…”
Section: General Characteristics Of Research Subjectssupporting
confidence: 75%
“…Un tercio de los adolescentes con obesidad tuvieron un diagnóstico de SM, mientras que 1 de cada 8 de los adolescentes con sobrepeso tuvieron SM. Esto coincide con lo que se ha informado en otros estudios donde la prevalencia de SM, diagnosticado también con el uso de los criterios de la IDF, varía del 20.8 al 55.8% en adolescentes con obesidad 14,15 y del 0.9 al 3.0% en adolescentes con peso saludable 6,[14][15][16][17] . Prevalencias mayores de SM, diagnosticado con los criterios del Adult Treatment Panel III, han sido reportadas en otros estudios de adolescentes con obesidad, uno de los cuales se realizó en población mexicana, en la región oeste y otro en adolescentes brasileños (62.0 y 45.5%, respectivamente) 7,17 .…”
Section: Materials Y Métodosunclassified
“…El sobrepeso, la obesidad y el SM son trastornos metabólicos que causan alteraciones en la secreción de insulina acompañadas de resistencia a la insulina 6 . Inicialmente, la resistencia a la insulina crea mecanismos compensatorios, mediante los cuales las células β-pancreáticas aumentan la producción y secreción de insulina, lo que mantiene una tolerancia a la glucosa normal, sin embargo, esta situación se agrava progresivamente hasta que la célula β no solo es incapaz de mantener la hipersecreción de insulina, sino que esta empieza a deteriorarse, con la consecuente disminución en la secreción de insulina 7 .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…The majority of the studies observed a positive association between total and abdominal body fat with insulin resistance (10). However, there are limited studies assessing the effect of other body composition compartments as fat-free mass.…”
Section: Introductionmentioning
confidence: 99%